Utilization of bark tannins from oriental spruce and oak in bioadhesive production - Gönültaş, Oktay; Uçar, Mualla (Isparta Uygulamalı Bilimler Üniversitesi, 2019)
In this research, bio-based tannin adhesives were developed by using tannins from spruce (Picea orientalis) and oak (Quercus spp.). The barks were obtained from wood-based panel industry and forest residues. The tannin powders were produced with a spray dryer based on the observations during the extraction process. Chemical analyzes were performed to determine the phenolic content of the spruce and oak tannins. After that bioadhesive synthesis experimentals were carried out using the spruce and oak tannins. In the experimentals, the bioadhesive synthesis parameters such as pH, formaldehyde:tannin molar ratio, viscosity, and free formaldehyde content were optimized. Finally, the adhesion performances of the bioadhesives were determined with the lap shear test. The results obtained in this work clearly showed that the shelf life and free formaldehyde content values of the adhesives were affected by the formaldehyde:tannin molar ratios. As for the maximum shelf life values of the bioadhesives, the spruce tannin adhesive had 72 days shelf life, whereas the oak tannin adhesive had 38 days. The gelation time values related with pH were also examined. The findings demonstrated that the spruce and oak sulfited tannins had 12% higher gelation time values than those of the water tannins. According to the results of the lap shear test, the spruce tannin based bioadhesives had similar adhesion performance as compared with a commercial phenol formaldehyde adhesive.

Bu çalışmada, biyobazlı tanen tutkalı üretimi yapılmıştır. Biyotutkal sentezinde kullanılan tanenler orman işletmelerinde kesim sonrası ortaya çıkan ladin (Picea orientalis) kabuğu ve ahşap levha endüstrisinde üretim sonrası ortaya çıkan atık meşe (Quercus spp.) kabuklarından elde edilmiştir. Ekstraksiyon sonrası elde edilen çözeltiler kullanılarak sprey kurutucuda toz tanen üretimi yapılmıştır. Üretilen ladin ve meşe tanenlerinin fenolik bileşimini ortaya koymak için tanen analizleri gerçekleştirilmiştir. Sonraki aşamada ladin ve meşe taneni kullanılarak biyotutkal sentez denemeleri yapılmıştır. Bu denemelerde sıcaklık, pH, formaldehit tanen molar oranı, viskozite, serbest formaldehit miktarı gibi parametreler optimize edilmiştir. Ardından üretilen tutkalın özellikleri ortaya konmuştur. Son olarak biyotutkalın yapışma performansı lap shear testi ile belirlenmiştir. Biyotutkal üretim denemeleri sonuçlarına göre, formaldehit tanen molar oranının tutkaldaki serbest formaldehit miktarı ve tutkalın raf ömrü üzerinde oldukça etkili olduğu anlaşılmıştır. Sentezlenen biyotutkal formülasyonlarında ladin için en yüksek raf ömrü 72 gün iken meşe için 38 gün olarak gerçekleşmiştir. pH’a bağlı jel zamanı değişimi de incelenmiş, ladin ve meşe sülfit tanenlerinin su taneninden %12 daha yüksek jel zamanına sahip olduğu ortaya konulmuştur. Lap shear testi sonuçlarına göre, ladin tanen tutkalı ticari fenol formaldehit tutkalına benzer yapışma performansına sahip olduğu görülmüştür.
Doğu ladini ve meşe kabuk taneninin biyotutkal üretiminde kullanılması
T-22881
Keywords: Engineering; Mühendislik